Numerical Methods for the Maxnear Criterion of Multiple-Sets Canonical Analysis (Journal of Mathematical Study, 2018)
This paper deals with numerical methods for the Maxnear criterion of multiple-setscanonical analysis. Optimality conditions are derived. Upper and lower boundsof the optimal objective function value are presented. Two iterative methods are proposed.One is an alternating variable method, and the other called Gauss-Seidel methodis an inexact version of the alternating variable method. Convergence of these methodsare analyzed. A starting point strategy is suggested for both methods. Numericalresults are presented to demonstrate the efficiency of these methods and the startingpoint strategy.
Keywords: Multiple-sets canonical analysis; Maxnear criterion; alternating variable method; starting point strategy.